2017
DOI: 10.1503/cjs.010116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrospun scaffolds of di-O-butyrylchitin and poly-(ε-caprolactone) on wound healing

Abstract: Background:We sought to determine the usefulness of electrospun dibutyrylchitin (DBC) or poly-(ε-caprolactone [PCL]), in wound treatment. We investigated the mechanisms of action of these polymers on wound healing. Methods:We synthesized DBC, a newly identified ester derivative of chitin, using a patented method comprising the substitution of butyryl groups at positions C-3 and C-6 in chitin molecules. We confirmed the double substitution by the butyric groups using infrared spectrometry. The fibrous scaffolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In the early stage, it accelerated the epithelisation process, it evoked slight inflammatory effect with delicate granulocytes induction (eosins connected to inflammation reaction), reduced the effusion phase and accelerated the creation phase. Similar histological image for the healing process was shown for the tests in which di-O-butyryl chitin (DBC) was used [47], and in which delicate inflammatory effect with macrophages presence, increase of vascularisation and then fibrosis was observed.…”
Section: Resultssupporting
confidence: 54%
“…In the early stage, it accelerated the epithelisation process, it evoked slight inflammatory effect with delicate granulocytes induction (eosins connected to inflammation reaction), reduced the effusion phase and accelerated the creation phase. Similar histological image for the healing process was shown for the tests in which di-O-butyryl chitin (DBC) was used [47], and in which delicate inflammatory effect with macrophages presence, increase of vascularisation and then fibrosis was observed.…”
Section: Resultssupporting
confidence: 54%
“…A slight decrease in wound size demonstrated that the toxic effect of Ag nanoparticles dramatically diminishes the healing capability of PCL. In fact, PCL improves wound healing through the induction of macrophage-mediated reactions, which produces growth factors [83].…”
Section: In Vivo Wound Healingmentioning
confidence: 99%
“…Nanofibers alone were also able to enhance cell attachment and proliferation through ECM scaffold mimicry while the addition of various growth factors promoted re‐epithelialization and angiogenesis 43 . Drobnik et al explored the efficacy of DBC and PCL scaffolds using murine models, of which both materials increased wound granulation tissue, improved hydration, and angiogenesis 78 . Beneficial effects are also seen in diabetic wounds where hybrid nanofibers functionally replace the lost ECM to facilitate fibroblasts and keratinocytes growth and actions 79 .…”
Section: Nanomaterials and Wound Healingmentioning
confidence: 99%
“…43 Drobnik et al explored the efficacy of DBC and PCL scaffolds using murine models, of which both materials increased wound granulation tissue, improved hydration, and angiogenesis. 78 Beneficial effects are also seen in diabetic wounds where hybrid nanofibers functionally replace the lost ECM to facilitate fibroblasts and keratinocytes growth and actions. 79 Other substances such as beta-glucan and PVA-PEG hybrid hydrogels were also feasible combinations that provided significant improvements in animal wound models.…”
Section: Nanofibers and Hydrogelsmentioning
confidence: 99%